Event Management System for Faculty of Mathematics and Natural Sciences Organizers - Agung Prajuhana Putra; Lita Karlitasari (LPPM Universitas Islam 45 Bekasi, 2024)
The advancement of technology in today's era has led to increased demands across various sectors, including Event Organizer (EO) Professional Service Providers. As a pivotal institution in scientific and academic advancement, the Faculty of Mathematics and Natural Sciences (FMIPA) at Universitas Pakuan regularly hosts a multitude of events ranging from seminars to workshops. However, the complexity of managing these events, exacerbated by varying participant numbers, presents substantial logistical, administrative, and communication challenges. FMIPA has witnessed a surge in event frequency and complexity in tandem with the growth in student enrollment, research, and academic collaboration. This paper underscores the critical importance of effective event management at FMIPA, emphasizing the necessity for an integrated and structured Event Organizer Management System. This system aims to address challenges such as team coordination, budget monitoring, and post-event reporting. By acknowledging the dynamic educational landscape and the imperative to meet high-quality standards, this research aims to contribute positively to FMIPA's institutional development. The proposed system seeks to enhance efficiency, effectiveness, and the overall impact of each scientific activity. Focusing specifically on FMIPA's logistical and administrative challenges during event organization, this study aims to design, develop, and implement an Event Organizer Management System tailored to FMIPA's unique requirements. The system targets improved event planning, streamlined participant registration, and structured logistics coordination, ultimately aiming to elevate operational efficiency and event quality. The success of the system hinges upon user involvement throughout the development cycle, ensuring alignment with FMIPA's evolving needs and fostering a culture of continuous improvement. Through this research, concrete solutions are expected to emerge, enhancing FMIPA's academic competitiveness and institutional standing.